2020
DOI: 10.1080/14756366.2020.1783664
|View full text |Cite
|
Sign up to set email alerts
|

Novel piperidine derivatives as colchicine binding site inhibitors induce apoptosis and inhibit epithelial-mesenchymal transition against prostate cancer PC3 cells

Abstract: Tubulin polymerisation inhibitors that target colchicine binding site were powerful anticancer agents. Although along the years many colchicine binding site inhibitors (CBSIs) have been reported, few piperidine derivatives were identified as CBSIs. In this regard, we focussed efforts on the piperidine as a promising chemotype to develop potent CBSIs. Herein, novel piperidine derivatives were synthesised and evaluated for their antiproliferative activities. Among them, compound 17a displayed powerful anticancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Several piperidine derivatives were synthesized among them one such derivative is compound 17a, which shows good anti-prostate cancer activity. Fu et al (2020) studied the effect of compound 17a on PC3 (prostate cancer cell line) and found that it inhibits PC3 proliferation in a concentrationdependent manner. Compound 17a also resulted in inducing apoptosis in PC3 cells by decreasing the expression level of XIAP and BCL-2 and increasing the level of BAX accordingly in a concentration-dependent manner (Samykutty et al, 2013).…”
Section: Anti-prostate Cancer Effect Of Piperidine and Its Mechanism Of Actionmentioning
confidence: 99%
“…Several piperidine derivatives were synthesized among them one such derivative is compound 17a, which shows good anti-prostate cancer activity. Fu et al (2020) studied the effect of compound 17a on PC3 (prostate cancer cell line) and found that it inhibits PC3 proliferation in a concentrationdependent manner. Compound 17a also resulted in inducing apoptosis in PC3 cells by decreasing the expression level of XIAP and BCL-2 and increasing the level of BAX accordingly in a concentration-dependent manner (Samykutty et al, 2013).…”
Section: Anti-prostate Cancer Effect Of Piperidine and Its Mechanism Of Actionmentioning
confidence: 99%
“…Colchicine is a microtubule inhibitor that can bind to tubulin dimers to prevent tubulin conversion and was found to prevent cell division during mitosis in vitro [ 21 ], which is one of the major factors causing liver toxicity. Previous studies on hepatotoxicity demonstrated that colchicine regulated the ubiquitin–proteasome pathway 3 to induce Mallory bodies [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It restricted the cell cycle in the G0/G1 phase [ 44 ]. Piperidine also inhibited prostate cancer cell growth by the induction of apoptosis [ 45 ]. It increased the levels of pro-apoptotic Bax and decreased the expression of BcL-2 and XIAP [ 24 ].…”
Section: Plant-based Food Componentsmentioning
confidence: 99%